Consumer Co-Creation and Its Impact on Brand Innovation in Digital Platforms - Hardianto, Hardianto (Journal of Social Commerce, 2023)
This study examines the effects of consumer co-creation on brand innovation within digital platforms from consumer co-creation activities such as idea generation, feedback provision, and co-design in a quantitative research study. Drawing on a heterogeneity of activities of digital platform users, the study maps and analyses the interference of such activities on multiple dimensions of innovation from novelty to market success. That is the results show that feedback provision has the strongest influence on innovation outcome, followed by idea generation and subsequently by collaborative design. Furthermore, the present research emphasizes on use of digital platforms and degree of engagement on innovation perception, showing that social platform and high degree of engagement was significantly favorably inclined. To some extent, this work fills the gaps which are present in the literature and identified earlier, by presenting the comparative analysis of co-creation activities and their efficiency, as well as by providing recommendations for practitioners and further investigation of the matter regarding the role and influence of co-creation in various settings.